Nociceptin/orphanin FQ and stress regulate synaptophysin expression in the rat fundic and colonic mucosa. Issue 2 (April 2015) - Grandi, Daniela; Becchi, Gabriella; Guerrini, Remo; Calò, Girolamo; Morini, Giuseppina
Graphical abstract: Highlights: Stress increases immunostained nerve fibers in the fundus. 4 h infusion of nociceptin/orphanin FQ increases immunostained fibers in the fundus. Immunostained cells are increased in the fundus of NOP (−/−) rats. Immunostained fibers are decreased in the fundus and colon of NOP (−/−) rats. Abstract: Nociceptin/orphanin FQ (N/OFQ), the endogenous ligand of the N/OFQ peptide (NOP) receptor, is a neuropeptide regulating gastrointestinal functions. The present study investigated the influence of acute cold-restraint stress and of short- and long-lasting peripheral infusion of N/OFQ on the level of synaptophysin, an exocytotic protein involved in neural plasticity. Exposure to cold-restraint stress for 3 h or subcutaneous infusion of N/OFQ, 1 μg/kg/h for 4 h, induced a significant increase of the area of synaptophysin-immunoreactive nerve fibers in the fundic mucosa, while prolonged subcutaneous infusion of N/OFQ, 1 μg/kg/h for 52 h and for 14 days, did not modify the synaptophysin-immunostained fibers. In the colonic mucosa stress exposure and subcutaneous infusion of N/OFQ, at any time point considered, had no significant effect on the area of synaptophysin-immunoreactive nerve fibers. Synaptophysin immunoreactive nerve fibers were decreased in knockout rats for the NOP receptor gene both in the fundic and colonic mucosa. Synaptophysin-immunoreactivity was demonstrated in cells located in the basal portion of the fundic mucosa. Our study is the first to show that the N/OFQ/NOP receptor system influences the expression of synaptophysin and hence the process of exocytosis both in nerve terminals and in cells.